Comparison of charging systems for electric vehicles and their impact on electrical grid - Monteiro, Vítor Duarte Fernandes (2012)
This paper presents a comparison of four types of on-board batteries charging systems for Electric Vehicles (EVs) and Plug-in Hybrid Electric Vehicles (PHEVs), and their impact on the power quality of the electrical power grid. In the comparison are analyzed the features, the characteristics and the operation of each charging system, aiming their controllability and their impact on the electrical grid, mainly considering the Total Harmonic Distortion (THD) of the consumed current and the power factor. Besides the normal mode of operation to charge the batteries, denominated Grid-to-Vehicle (G2V), in this paper is also discussed the possibility of operation as Vehicle-to-Grid (V2G), in which the batteries of the Electric Vehicle return part of the stored energy back to the electrical grid. The operation of the batteries charging systems for EVs is shown through simulations and experimental results.